Neznosna lahkost avtohtonosti? - Stergar, Janez (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
UNBEARABLE LIGHTNESS OF AUTOCHTHONISM? Autochthonism as the constitutional criterium for the definition or constituting of a national minority should not be taken lightly or underrated, not even in very fundamental theoretical discourses. The majority of - indeed non-standardized - definitions of national minority do give consideration to a certain form of autochthonism, of traditional or lengthy connectedness with the territory of classical or historic national minorities, which had not been migrating, but were separated, due to historic events, from their parent nation by a state border.At the very beginning of formation of European minority documents, classical national minorities were clearly distinguished from migrants, asylum seekers, refugees, Roma - travellers and other new minorities . To establish an antagonism between the special rights of each of these deprivileged groups and the fundamental human rights of each individual is an unproductive deed.
Keywords: Slovenia; Slovenija; avtohtonost; narodne manjšine; zaščita manjšin